Bleomycin and Olaparib Induced Modulation of Poly (ADP-Ribose) Polymerase 1 Activity and Chromatin Structure in Thymocyte Nuclei (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: Poly (ADP-ribose) polymerase 1 inhibitors (PARPi) are used in the treatment of cancer patients asmonotherapy agents or in combination with approved anticancer drugs to optimize their clinical use. However,the development of novel anticancer chemotherapy is tempered by the potential detrimental side effects displayedby cytotoxic drugs in healthy cells. To delineate the rationality of PARPi olaparib (OLA) in combination with theapproved DNA-damaging anticancer drug bleomycin (BLM), we investigated the influence of the drugs on poly(ADP-ribose) polymerase 1 (PARP 1) activity, chromatin, and DNA structure in healthy rat thymocyte nuclei.Materials and Methods: Wistar albino male rats (Rattus norvegicus, 6 weeks old) were used throughout theexperiments. Animals were obtained from the stock of the animal house of the faculty of biology at YSU. Theenzymatic assay for PARP 1 activity was performed according to the original method based on the estimationof residual NAD+ concentration in the PARP assay mix adapted by us to quantify NAD+ consumed by isolatednuclei. DNA concentrations were measured by the spectrophotometric method using an extinction coefficientε260=6600 M-1 cm-1. Statistical differences in results between groups were evaluated by the Student’s t-test. P < 0.05was considered significant. Key Results: It was observed that in healthy rat thymocyte nuclei, BLM inducedPARP-1 inhibition and DNA and chromatin loosening. In contrast, treatment with OLA maintained chromatin andDNA condensation, which could partly underlie the cytotoxic effect of OLA as a result of drug-induced downregulationof chromatin-associated nuclear functions. Our findings provide evidence for the revalidation of therationality of OLA application in combination chemotherapy regimens involving BLM.